2016
DOI: 10.1111/jcmm.12935
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial toxicity and caspase activation in HIV pregnant women

Abstract: To assess the impact of HIV‐infection and highly active anti‐retroviral treatment in mitochondria and apoptotic activation of caspases during pregnancy and their association with adverse perinatal outcome. Changes of mitochondrial parameters and apoptotic caspase activation in maternal peripheral blood mononuclear cells were compared at first trimester of pregnancy and delivery in 27 HIV‐infected and ‐treated pregnant women versus 24 uninfected pregnant controls. We correlated immunovirological, therapeutic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(76 reference statements)
2
8
0
Order By: Relevance
“…[ 12 ] Although the numbers are small to draw conclusions, it may be a matter of concern if confirmed in other studies with larger number of PHIV women. Further studies are needed to determine the causal mechanisms and the possible role of long-term exposure to ART [ 36 ] and chronic inflammation. [ 37 ] HIV-exposed children born SGA may thus warrant an appropriate follow-up throughout adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] Although the numbers are small to draw conclusions, it may be a matter of concern if confirmed in other studies with larger number of PHIV women. Further studies are needed to determine the causal mechanisms and the possible role of long-term exposure to ART [ 36 ] and chronic inflammation. [ 37 ] HIV-exposed children born SGA may thus warrant an appropriate follow-up throughout adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…We included 5 observational studies among which four cross sectional studies and one prospective cohort study [5,7,8,12,13] (Table 1). The results were reported narratively.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies included double-NRTI based regimens. Among them, three studies included AZT contained regimens [5,7,8]. As explained above, AZT based regimens may cause severe mitochondrial deflections implying highly statistically significant results in AZT based regimens studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects observed in male HIV patients on HAART regimen include histopathological changes such as seminiferous tubules atrophy, and alteration in semen parameters including reduced sperm motility and altered sperm mitochondrial DNA ( Pavili et al., 2010 ; Savasi et al., 2019 ). Conflicting results have been reported on female HIV patients receiving the HAART; some studies reported no negative effects either on the reproductive system or the foetus ( Patel et al., 2005 ; Myer et al., 2010 ; Kushnir and Lewis 2011 ) while other studies reported impaired oocyte mitochondrial DNA that may lead to reduced fertility ( Lopez et al., 2008 ; Kushnir and Lewis 2011 ; Hernandez et al., 2017 ). Research data on rats treated with ARVs and their combinations have reported testicular alterations including degeneration of seminiferous tubules as well as a decrease in sperm motility in male rats ( Azu et al., 2014 ; Awodele et al., 2018 ; Oyeyipo et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%